Profile of Mortalities due to Alcohol and Drug Consumption in Road and Rail Traffic Accidents in Mangaluru, a Coastal City of Karnataka, India (Medico Legal Update, 2019)
Objective: Several studies have demonstrated that driving under influence of alcohol and psychoactive drugs increases the risk of fatal accidents & hence increased mortality rates. This paper presents a retrospective study of Road & Rail traffic accidents in Mangaluru.Method: Over a six-year period (2010-2015), a total of 5226 autopsies were conducted at Govt. Wenlock Hospital, Mangaluru out of which 1261 were Vehicular accidents (1117 - Road, 144 - Rail) .Various parameters were looked in these cases such as age groups, gender, type of Vehicle involved, Victim status, time of day, day of the week (weekdays/weekend), Season, type of intoxication, accident site etc.Results: 15.85% (n = 177) of all the Road Traffic Deaths & 9.72% (n=14) of all Rail deaths occurred as a consequence of either alcohol (16.83%, n=188/191) or drug overdose (n=3). 42.93% of victims belonged to 56 and above age group. Most commonly the e the vehicle which were involved in accident were motorcycles (around 51.83% cases).Conclusions: The results of this study reveals a strong positive association between the presence of alcohol and psychoactive drugs in road & rail traffic accident victims. The matter of grave concern is increasing trend of drunken driving leading to fatal accidents among adolescent age-groups especially in motorcycle vehicles.